2019
DOI: 10.1103/physrevc.100.045201
|View full text |Cite
|
Sign up to set email alerts
|

Spin-isospin Kondo effects for Σc and Σc* baryons and D¯

Abstract: We study the Kondo effect for a c ( * c ) baryon in nuclear matter. In terms of the spin and isospin [SU(2) spin × SU(2) isospin ] symmetry, the heavy-quark spin symmetry and the S-wave interaction, we provide the general form of the Lagrangian for a c ( * c ) baryon and a nucleon. We analyze the renormalization equation at the oneloop level and find that the coexistence of spin exchange and isospin exchange magnifies the Kondo effect in comparison with the case where the spin-exchange interaction and the isos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…Such "relativistic" Kondo effects can occur in relativistic-fermion systems including impurities, such as graphene (see Ref. [6] for a review), Dirac/Weyl semimetals [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], dense nuclear matter [24][25][26][27], and dense quark matter [13,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Among them, the QCD Kondo effect [24,28] is induced by the color exchange interaction between a light quark and an impurity quark, which is based on quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%
“…Such "relativistic" Kondo effects can occur in relativistic-fermion systems including impurities, such as graphene (see Ref. [6] for a review), Dirac/Weyl semimetals [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], dense nuclear matter [24][25][26][27], and dense quark matter [13,24,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Among them, the QCD Kondo effect [24,28] is induced by the color exchange interaction between a light quark and an impurity quark, which is based on quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%
“…The Kondo effect is expected to arise also in the hadronic phase at lower density. In fact, it was shown that the Kondo effect arises in nuclear matter when Σ c and Σ * c baryons or D and D * mesons exist as impurities, where the spin and/or isospin exchange serves as the non-Abelian interaction [3,[5][6][7]. In addition, many works on Kondo effect in a relativistic system have been done in the literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in heavy hadrons was renewed as the experiments on them including exotic heavy hadrons have yielded unprecedented findings [18][19][20][21][22] (see a recent review for the status of experiments on nonstandard heavy hadrons [23]). This has also triggered the investigation on heavy baryons in nuclear matter [24][25][26][27][28][29] (see also a review [30]). Since there are no experimental data on how the heavy baryons undergo changes in nuclear medium and in nuclei, it is of great importance to study the medium modification of them theoretically to guide future experiments.…”
Section: Introductionmentioning
confidence: 99%